Is Merkel Cell Carcinoma of Lymph Node Actually Metastatic Cutaneous Merkel Cell Carcinoma?. Issue 3 (23rd May 2020) - Lawrence, Lauren E B; Saleem, Atif; Sahoo, Malaya K; Tan, Susanna K; Pinsky, Benjamin A; Natkunam, Yasodha; Kunder, Christian A; Stehr, Henning; Zehnder, James L
Abstract: Objectives: The possibility of a so-called primary lymph node neuroendocrine carcinoma has been described in the literature. Here we evaluate cases fitting such a diagnosis and find that the cases demonstrate a convincing and pervasive pattern consistent with metastatic Merkel cell carcinoma. Methods: Six cases of primary lymph node Merkel cell carcinoma and one case of metastatic neuroendocrine carcinoma at a bony site, all with unknown primary, were sequenced using a combination of whole-exome and targeted panel methods. Sequencing results were analyzed for the presence of an ultraviolet (UV) mutational signature or off-target detection of Merkel cell polyomavirus (MCPyV). Results: Four of six primary lymph node cases were positive for a UV mutational signature, with the remaining two cases positive for off-target alignment of MCPyV. One case of neuroendocrine carcinoma occurring at a bony site was also positive for a UV mutational signature. Conclusions: We find no evidence to corroborate the existence of so-called primary Merkel cell carcinoma of lymph node.